Объяснение:
1)формула: sin2a=2sina*cosa, по этой формуле sina=sin2*(a/2)=
2sin(a/2)*cos(a/2), тогда sin^2 a=4sin^2 (a/2)*cos^2 (a/2),это в числителе,
формула 1-cosa=2sin^2 (a/2),
=4sin^2 (a/2)*cos^2 (a/2) / -(2sin^2 (a/2)) =-2cos^2 (a/2)
2) формула cos^2 a=1-sin^2 a,
=cos^2 a+cos^2 a*cos^2 a/sin^2 a= (приводим к общему знаменателю)
=(сos^2 a*sin^2 a+cos^2 a*cos^2 a) /sin^2a=cos^2 a*(sin^2 a+cos^2 a)/
sin^2 a=cos^2 a*1 /sin^2 a=ctg^2 a
Объяснение:
1)формула: sin2a=2sina*cosa, по этой формуле sina=sin2*(a/2)=
2sin(a/2)*cos(a/2), тогда sin^2 a=4sin^2 (a/2)*cos^2 (a/2),это в числителе,
формула 1-cosa=2sin^2 (a/2),
=4sin^2 (a/2)*cos^2 (a/2) / -(2sin^2 (a/2)) =-2cos^2 (a/2)
2) формула cos^2 a=1-sin^2 a,
=cos^2 a+cos^2 a*cos^2 a/sin^2 a= (приводим к общему знаменателю)
=(сos^2 a*sin^2 a+cos^2 a*cos^2 a) /sin^2a=cos^2 a*(sin^2 a+cos^2 a)/
sin^2 a=cos^2 a*1 /sin^2 a=ctg^2 a